2021
DOI: 10.1186/s12889-021-11470-9
|View full text |Cite
|
Sign up to set email alerts
|

Diarrhoeal diseases in Soweto, South Africa, 2020: a cross-sectional community survey

Abstract: Background In South Africa, there are limited data on the burden of diarrhoea at a community level, specifically in older children and adults. This community survey estimated rates of and factors associated with diarrhoea across all ages and determined the proportion of cases presenting to healthcare facilities. Methods Households were enrolled from an existing urban health and demographic surveillance site. A household representative was interview… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 20 publications
0
1
1
Order By: Relevance
“…This finding is higher than studies conducted elsewhere in the SADC region (6,16). A study conducted in a South African low-and middle-income township (Soweto) found a diarrheal disease prevalence of 20.9% among children under-5 years old (16). This study's prevalence was higher when compared to a study in Mozambique with a similar population that find a prevalence of 10.6%.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…This finding is higher than studies conducted elsewhere in the SADC region (6,16). A study conducted in a South African low-and middle-income township (Soweto) found a diarrheal disease prevalence of 20.9% among children under-5 years old (16). This study's prevalence was higher when compared to a study in Mozambique with a similar population that find a prevalence of 10.6%.…”
Section: Discussioncontrasting
confidence: 72%
“…In this study, the prevalence of childhood diarrheal diseases was 22.5% over two weeks. This finding is higher than studies conducted elsewhere in the SADC region (6,16). A study conducted in a South African low-and middle-income township (Soweto) found a diarrheal disease prevalence of 20.9% among children under-5 years old (16).…”
Section: Discussionmentioning
confidence: 64%
“…Soweto, a sprawling urban settlement in Johannesburg, is South Africa's biggest township. It has a projected 1.6 million residents, occupying 355,331 households (2019 census) [7,8]. Johnstone et al [7] reported that Soweto has a diarrhoeal prevalence rate of 5.3%, with children more likely to present to the hospital compared to adults.…”
Section: Introductionmentioning
confidence: 99%
“…It has a projected 1.6 million residents, occupying 355,331 households (2019 census) [7,8]. Johnstone et al [7] reported that Soweto has a diarrhoeal prevalence rate of 5.3%, with children more likely to present to the hospital compared to adults. The majority of Soweto's population live in informal settlements [8], and between 600,000 and 1,000,000 residents live in abject poverty [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation